Multi-omics-based insights into the microbial community composition and quality characteristic differentiation potential between Xuanwei and Iberian dry-cured hams - Nannan Zhou; Jiayan Tan; Shuai Tang; Yanfei Du; Wen Xun; Yucai Yang; Jiao Li; Chunying Weng; Kesi Yang; Huiwen Dong; Enyong Pu; Guozhou Liao; et al. (International Journal of Food Microbiology, 2026)

Thermal degradation mechanism of the 1,2,3-trichlorobenzene as PCDD/Fs precursor by waste polyurethane - Pu Lyu; Yun Xue; Jinhui Li; Dongliang Zhao; Yifei Sun; Linpeng Du; Yuan Chen; Jia Peng; Xiaohua Zhu; Songtao Yang; Huanliang Lu; Peiling Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Elucidation of microbial community structure, small-molecule metabolic and flavor profile characteristics in Xuanwei ham under different processing techniques - Nannan Zhou; Wen Xun; Jiao Li; Yanfei Du; Yucai Yang; Jiayan Tan; Shuai Tang; Kesi Yang; Chunying Weng; Huiwen Dong; Enyong Pu; Guozhou Liao; et al. (Food Research International, 2026)

Sulfate ester motifs of carrageenan govern the assembly and functional properties of tea protein carriers - Xinran Liu; Jinhua Song; Zongwei Hao; Yang Pu; Lihua Chu; Zhongwen Xie; Daxiang Li; Zhenyu Yu; Yiqun Du (Food Chemistry, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

Metal-silicate partitioning behaviors of Ga and Ge at high pressures and implications for the Earth’s volatile accretion - Zhengyang Wu; Chang Pu; Xiujin Gao; Jinfeng Li; Zhixue Du; Zhicheng Jing (Geochimica et Cosmochimica Acta, 2026)

Effect of Submarine Speed on Its Motion in Internal Solitary Waves - Maolin Wang; Hui Du; Shaodong Wang; Tianyu Zhang; Pu Xuan; Pai Peng; Ruipeng Li; Zhan Wang (Journal of Marine Science and Engineering, 2026)
Although extensive research has been carried out on the load characteristics of fixed submarines in internal solitary waves, there is still insufficient understanding of the effect of submarine speed on its motion in internal solitary waves. A rapid calculation method for the motion response of a submarine (SUBOFF standard model) in internal solitary waves between two layers of fluid is established in this study, where the internal wave flow field is constructed based on the extended Korteweg-de Vries theory, and the load on the submarine is calculated using the Morison equation. The accuracy of the proposed method is verified by comparison with numerical results and experimental data. The results of the motion response of the submarine when encountering internal solitary waves at different speeds show that there is a significant nonlinear relationship between speed and vertical motion amplitude and maximum pitch angle. A critical speed is further found, beyond which the submarine experiences a secondary falling deep after the initial vertical falling deep.

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

Investigation on enhanced oil recovery potential of active nano-SiO2 in high-temperature and high-salinity reservoirs at core and pore scale - Daijun Du; Shuaikang Hou; Wanfen Pu; Qingxia Li; Yangyang Zhang; Bowen Li; Yu He; Yingxue Xu; Peiwen Xiao (Fuel, 2026)

TS-TCN: a deep learning model for ultra-short-term outdoor air temperature forecasting in complex terrain with small sample size - Shun Wu; Jie Shao; Ge Li; Xiushu Pu; YuanChang Dong; Tao Du; Jinrong Kang; Bu Zhao (Energy and Buildings, 2026)

C-Fos protein expression in the mouse brain: effects of nicotine aerosol - Ying Li; Shanshan Du; Jingping Sun; Xiaodong Guo; Qidong Zhang; Pu Fan; Yufei Hu; Jian Mao; Wu Fan; Qingzhao Shi; Guobi Chai; Jianping Xie (Toxicology and Applied Pharmacology, 2025)

Teleost-specific TLR25/MyD88 signaling promotes K63-linked ubiquitination of IRF1 to induce IFNa gene expression - Yunkun Li; Shihui Yi; Wuhao Tang; Lei Shi; Huizhen Yan; Lei Ning; Jing Pu; Kanbei Shiyi; Lanxin Zhang; Xiaoshuang Chen; Jiayun Wu; Shiyong Yang; et al. (Fish & Shellfish Immunology, 2025)

Compressive behavior of masonry column confined reinforced with ECC and GFRP grids - Tong Hao; Jingyi Shen; Pu Zhang; Bin Du; Zongze Li; Erjun Peng; Enfeng Deng (Engineering Structures, 2025)

Modeling feedback-driven behavioral adaptation in pigs under environmental pressure: a study of behavior modification - Zhen Wang; Yunying Liu; Geqi Yan; Xinyi Du; Fei Qi; Zhengxiang Shi; Chaoyuan Wang; Hao Li; Hao Wang; Shihua Pu (The Veterinary Journal, 2025)

Data-driven insights to tackle photo-induced phase segregation for mixed-halide perovskite solar cells - Yuhui Jiang; Yu Zheng; Jingfan Li; Yang Pu; Liming Du; Yangyang Guo; Ning Jia; Xu Zhang; Yerzhan Mukhametkarimov; Ruihao Chen; Zhe Liu; Hongqiang Wang (Chemical Engineering Journal, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Channel attention residual transfer learning with LLM fine-tuning for few-shot fault diagnosis in autonomous underwater vehicle propellers - Wenliao Du; Xinlong Yu; Zhen Guo; Hongchao Wang; Yiyuan Gao; Ziqiang Pu; Guanghua Li; Chuan Li (Ocean Engineering, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

The community diversity and metabolic function of symbiont bacteria associated with soil amoebae (dictyostelids) in free-living habitats - Zhaojuan Zhang; Yingkun Yang; Yujing Du; Yue Zou; Steven L. Stephenson; Yu Li; Pu Liu (Applied Soil Ecology, 2025)

Enhancing underwater thruster anomaly detection with support vector glow encoding description - Wenliao Du; Zihan Xiong; Pengxiang Zhu; Ziqiang Pu; Chuan Li; Dongdong Hou (Ocean Engineering, 2024)

A novel in-silico strategy for the combined inhibition of intestinal bacterial resistance and the transfer of resistant genes using new fluoroquinolones, antibiotic adjuvants, and phytochemicals - Qikun Pu; Zhonghe Wang; Tong Li; Qing Li; Meijin Du; Wenwen Wang; Yu Li (Food Bioscience, 2024)

Characterization and fine mapping of a white stripe leaf mutant in rice - Binhua Hu; Zhiyuan He; Xiaoli Xiang; Hui Li; Anping Du; Mingxia Wang; Yulu Bai; Lanying Wang; Cong Zhang; Ping Wang; Zhigang Pu (Genetic Resources and Crop Evolution, 2024)

A deductive approach of 3D complex fault modeling and application - Yuchen Li; Yuanze Du; Qiang Wu; Jinhong Meng; Huawei Tian; Junwei Ke; Gengmeng Pu; Hua Xu (Bulletin of Engineering Geology and the Environment, 2024)

Lactobacillus delbrueckii ameliorates Aeromonas hydrophila-induced oxidative stress, inflammation, and immunosuppression of Cyprinus carpio huanghe var NF-κB/Nrf2 signaling pathway - Chunnuan Zhang; Changchang Pu; Shengnan Li; Ruiyi Xu; Qian Qi; Juan Du (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Experimental study on the flexural behaviors of ECC-reinforced masonry beams with GFRP mesh - Pu Zhang; Shilong Wang; Xianghua Tao; Zongze Li; Ye Liu; Erjun Peng; Bin Du; Jianmin Lv (Engineering Structures, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Single-cell and multi-omics analyses highlight cancer-associated fibroblasts-induced immune evasion and epithelial mesenchymal transition for smoking bladder cancer - Jiajin Wu; Fang Gao; Rui Meng; Huiqin Li; Zhenguang Mao; Yanping Xiao; Qiuyi Pu; Mulong Du; Zhengdong Zhang; Qiang Shao; Rui Zheng; Meilin Wang (Toxicology, 2024)

Improved microalgae carbon fixation and microplastic sedimentation in the lake through in silico method - Meijin Du; Qikun Pu; Yingjie Xu; Yu Li; Xixi Li (Science of The Total Environment, 2024)

Exposure estimation and neurotoxicity inhibition of dioxins in sensitive populations near domestic waste incineration plant through adverse outcome pathway - Qing Li; Yunxiang Li; Qikun Pu; Hao Yang; Meijin Du; Xinao Li; Yu Li; Xixi Li (Journal of Hazardous Materials, 2024)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Reduced bacterial resistance antibiotics with improved microbiota tolerance in human intestinal: Molecular design and mechanism analysis - Meijin Du; Zhixing Ren; Qing Li; Qikun Pu; Xinao Li; Youli Qiu; Yu Li (Journal of Hazardous Materials, 2023)

Effects and control mechanisms of ammonia, particulate matters and aerosol bacterial compositions in poultry houses by spray technology - Huaxuan Zhao; Shangmin Li; Junhua Pu; Hongzhi Wang; Xinhong Dou; Hongguang Liu; Juntao Liao; Lishun Du (Journal of Cleaner Production, 2023)

Assessing the occurrence and sources of synthetic additive pollutants in lake sediments using fecal and sewage markers - Rui Du; Xiaoxia Feng; Pu Wang; Ruiqiang Yang; Gang Li; Jianjie Fu; Yong Liang; Ting Ruan; Guibin Jiang (Environmental Pollution, 2023)

Exposure to outdoor artificial light at night increases risk and burden of metabolic disease in Ningxia, China - Huihui Wang; Xiaohong Ma; Zhenfan Yu; Naifan Hu; Yurun Du; Xiaoxue He; Degong Pan; Lining Pu; Xue Zhang; Xian Sun; Jiangping Li (Environmental Science and Pollution Research, 2023)

Long-term assessment on performance and seasonal optimal operation of a full-scale integrated multiple constructed wetland-pond system - Yashuai Pu; Yiping Li; Liqin Zhu; Yu Cheng; Linda A. Nuamah; Haikuo Zhang; Hongwei Chen; Guanchao Du; Ling Wang; Congqing Song (Science of The Total Environment, 2023)

Perfluoroalkyl and polyfluoroalkyl substances (PFAS) adsorbed on microplastics in drinking water: Implications for female exposure, reproductive health risk and its mitigation strategies through in silico methods - Meijin Du; Qikun Pu; Xixi Li; Hao Yang; Ning Hao; Qing Li; Yuanyuan Zhao; Yu Li (Journal of Cleaner Production, 2023)

Synthesis of bifunctional NiFe layered double hydroxides (LDH)/Mo-doped g-C3N4 electrocatalyst for efficient methanol oxidation and seawater splitting - Yufei Du; Yichu Zhang; Xunchi Pu; Xiaoying Fu; Xuan Li; Linqin Bai; Yongjun Chen; Jin Qian (Chemosphere, 2023)

New-type pliocene channel depositional systems resulting from turbidity flows obliquely interacting with contour currents: A novel case study from the southern Qiongdongnan basin, northern South China Sea - Yufeng Li; Renhai Pu; Gongcheng Zhang; Jiangmin Du; Jingjing Bao (Marine and Petroleum Geology, 2023)

How do the Growth and Metabolic Activity of Aquatic fungi Geotrichum Candidum and Aspergillus Niger Respond to Nanoplastics? - Wenrui Qv; Xilin Wang; Ningyun Li; Jingjing Du; Gaozhong Pu; Hongzhong Zhang (Bulletin of Environmental Contamination and Toxicology, 2022)

Association of outdoor artificial light at night with mental health among China adults: a prospective ecology study - Zhenfan Yu; Naifan Hu; Yurun Du; Huihui Wang; Lining Pu; Xue Zhang; Degong Pan; Xiaoxue He; Jiangping Li (Environmental Science and Pollution Research, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Identification of four functional component content QTLs of brown rice in the Yunnan mini-core collection and its near-isogenic lines using association mapping - Xia Li; Xiaomeng Yang; Juan Du; Zhiyuan Chen; Mingliang Wei; Xiaoying Pu; Jiazhen Yang; Tao Yang; Md. Siddikun Nabi Mandal; Lijuan Chen; Yawen Zeng (Cereal Research Communications, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Trace element distribution in tissues and risk of exposure of ruddy shelduck wintering in Nanhaizi Wetland, Baotou, China - Li Liu; Chao Du; Yan Sun; Jianqing Liu; Zihan Pu; Xiaoguang Liu (Environmental Science and Pollution Research, 2020)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Snowfall-related deterioration behavior of the Ming Great Wall in the eastern Qinghai-Tibet Plateau - Tianbiao Pu; Wenwu Chen; Yumin Du; Wenjuan Li; Na Su (Natural Hazards, 2016)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

Mass balance and near-surface ice temperature structure of Baishui Glacier No.1 in Mt. Yulong - Jiankuo Du; Yuanqing He; Shuang Li; Shijin Wang; Hewen Niu; Huijuan Xin; Tao Pu (Journal of Geographical Sciences, 2013)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Climate change and its effect on annual runoff in Lijiang Basin-Mt. Yulong Region, China - Yuanqing He; Tao Pu; Zongxing Li; Guofeng Zhu; Shijin Wang; Ningning Zhang; Shuxin Wang; Huijuan Xin; Wilfred H. Theakstone; Jiankuo Du (Journal of Earth Science, 2010)

QTLs of cold tolerance-related traits at the booting stage for NIL-RILs in rice revealed by SSR - Yawen Zeng; Shuming Yang; Hong Cui; Xiaojuan Yang; Liming Xu; Juan Du; Xiaoying Pu; Zichao Li; Zaiquan Cheng; Xingqi Huang (Genes & Genomics, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)